Atypical discrete papular lichen myxedematosus associated with monoclonal gammopathy: report of four cases and review of the literature. (16th July 2016) - Hermans, C.; Goldscheider, I.; Ruzicka, T.; Rongioletti, F.
Abstract: Background: Discrete papular lichen myxedematosus (DPLM) is a rare form of localized lichen myxedematosus that presents with skin involvement only and without systemic involvement. Object: To describe our experience with atypical cases of DPLM associated with monoclonal gammopathy. Methods: Data were collected from patients with clinicopathological evidence of DPLM associated with monoclonal gammopathy who presented to the Department of Dermatology of two tertiary university‐affiliated medical centres from 2000 to 2015 and were followed prospectively. Results: The sample included four patients (three males) with a mean age of 58 years. No clinicopathological differences from typical cases of DPLM were observed, except for the presence of monoclonal gammopathy. The patients were followed up for a mean of 34 months (6–72 months) and no progression to scleromyxedema, multiple myeloma or systemic involvement was observed. No therapy was applied, except for topical tacrolimus or steroids, and the eruptions remained stable. Conclusion: Our experience indicates an excellent prognosis of DPLM even for atypical cases in spite of the presence of monoclonal gammopathy.